New Strategic Approaches to Gaining from Emerging Advanced Manufacturing Markets - Yuri Simachev; Anna Fedyunina; Maksim Yurevich; Mikhail Kuzyk; Nikolay Gorodnyi (Foresight and STI Governance)
Advanced Manufacturing (AM) markets are a major factor of contemporary worldwide growth that to a large extent determines countries’ competitiveness. Strengthening and/or optimizing the positions on AM markets is among the major challenges for modern industrial policy. This article discusses the structure and dynamics of the development of advanced manufacturing markets, as well as the specifics of the policies of the countries strengthening their positions in these markets. Gaining entry into AM markets currently implies individual countries’ and industries’ adopting different models which combine a wide range of factors. Small nations are rapidly applying such approaches, gaining advantages and thus increasing their competitive edge, which creates certain challenges for leading high-tech countries too slow to adjust their industrial policies. So far the basis for Industry 4.0 markets is just emerging, and remains limited to a few nations including developing ones. Country cases are presented below to illustrate the development of AM markets.